FORMULATION OF POLITICAL HATE SPEECH THROUGH SOCIAL MEDIA IN PAKISTAN - Afifa Tanveer Malhi; Dr Muhammad Kamran khan; Tahira Aftab; Ansar Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
The study aims to examine how individual or group especially in the field of politics are generally, discursively and linguistically represented in social media application Facebook. It explores that due to deregulation in political Hate speech for social media, how current practice of new media is indifferent & unethical in our society. To analyze the political troll, the study uses the Critical Discourse Analysis (CDA) followed by the Political Hate speech related to media. The main focuses of the study is to inspect the news accuracy and online political hate matters, threat to integrity and disrespect and lack of responsibility. The analysis also examines the metaphors and name calling use against the politicians in the posts, status and comments on timeline of Facebook pages. The study leads to the conclusion that the users of Facebook, whether individual or media professionals, have been practicing against the hate speech of conduct by sustained and systematic troll against the political figures and their families that might lead to the rumors, character assassination and harm to popularity.